Theoretical Study of the Division of Semitic Language Dialects: The Types and functions in society - Makhisoh, Iis; Hasbullah, Abdur Rouf (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2021)
Since the late nineteenth century the concept of language has changed its nature, function and study. This change has brought about successive efforts made by Western scholars to study most of the world’s languages, descriptions, history and comparisons. As a result of these efforts in the linguistic field, the study of language became a science.Linguistics in its simplest definition is the study of language in a scientific way. This definition means that linguistic studies are objective and not subjective impressionism. And language has evolved over time, and some of its elements have changed as it spread due to internal or external causes. The language branched into dialects and languages ​​until linguistic factions arose in the world. And the language developed both phonetically and as a sign. This research speaks of the branching of languages ​​into dialects and then the formation of those dialects themselves with their types.There are languages that spread in large areas and in some case have become the language of the state. While languages do not spread and are used by only a few people.the reasons for the spread of languages into many types are (1) the clash of language in conflict with another language or languages, (2) the movement of members of the people, and (3) the availability of a group of reasons favorable to natural growth. Or in the opinion of the latest political, psychological, geographic, popular or physiological factors.